Soft magnetic powder and dust cores

JP7633825B2Active Publication Date: 2025-02-20TAMURA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021020736
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-12
Publication Date
2025-02-20
Estimated Expiration
2041-02-12

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、ヒステリシス損失の低減を図ることができる軟磁性粉末及び圧粉磁心を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633825000003
    Figure 0007633825000003
  • Figure 0007633825000004
    Figure 0007633825000004
  • Figure 0007633825000005
    Figure 0007633825000005
Patent Text Reader

Abstract

To provide a soft magnetic powder using pure iron powder that reduces hysteresis loss and a powder magnetic core containing this soft magnetic powder.SOLUTION: In a soft magnetic powder using a pure iron powder, the pure iron powder has a ratio of peaks of planes in all directions to a peak of plane index 110 in X-ray diffraction of 0.430 or less. The pure iron powder is water-atomized powder or gas-atomized powder, and the pure iron powder is used to form a powder magnetic core.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a soft magnetic powder using pure iron powder and a dust core containing this soft magnetic powder. [Background technology]

[0002] Coil components such as reactors are used in a variety of applications, including office equipment, solar power generation systems, and automobiles. Coil components have a coil attached to a core. Powder magnetic cores are often used for this core.

[0003] The dust core includes soft magnetic powder and an insulating layer formed around the soft magnetic powder, and is formed by compacting the soft magnetic powder with the insulating layer formed thereon. The pressure during compacting is quite high, ranging from several tons to several tens of tons, to compact the soft magnetic powder.

[0004] Due to requirements for improved energy exchange efficiency and low heat generation, powder magnetic cores are required to have magnetic properties that minimize energy loss when magnetic flux density changes. The magnetic property related to energy loss is specifically iron loss (Pcv). Iron loss (Pcv) is expressed as the sum of hysteresis loss (Ph) and eddy current loss (Pe). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5929819 Summary of the Invention [Problem to be solved by the invention]

[0006] Research has been conducted to reduce hysteresis loss. For example, research has been conducted to show that low hysteresis loss can be obtained when the crystal grains are coarse, as in Patent Document 1. However, in recent years, the applications of coil components have become more diverse, and further reduction in hysteresis loss is required.

[0007] The present invention has been made to solve the above problems, and an object of the present invention is to provide a soft magnetic powder and a dust core that can reduce hysteresis loss. [Means for solving the problem]

[0008] The soft magnetic powder of the present invention comprises pure iron powder, characterized in that the ratio of peaks of all planes in all directions to the peak with plane index 110 in X-ray diffraction is 0.430 or less.

[0009] A dust core containing the soft magnetic powder is also an aspect of the present invention. Effect of the Invention

[0010] According to the present invention, it is possible to obtain a soft magnetic powder and a dust core capable of reducing hysteresis loss. [Brief description of the drawings]

[0011] [Figure 1] 1 is a graph showing the relationship between the ratio of the peaks of all directional faces to the peak of a face index of 110 and non-uniform strain. [Diagram 2] 1 is a graph showing the relationship between non-uniform strain and hysteresis loss. [Diagram 3] 1 is a graph showing the relationship between the ratio of the peaks of all planes in all directions to the peak of a plane index of 110 and hysteresis loss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] (Embodiment) The soft magnetic powder in this embodiment will be described below. Note that the present invention is not limited to the embodiment described below.

[0013] Soft magnetic powder is used as a material for dust cores, which are the magnetic bodies in coil parts installed in office equipment, solar power generation systems, automobiles, etc. Dust cores are made by compacting soft magnetic powder surrounded by an insulating layer to form a compact, and then annealing this compact.

[0014] As the soft magnetic powder, pure iron powder is used. Pure iron powder contains 99% or more of Fe. It is preferable to use water atomized powder or gas atomized powder as the pure iron powder.

[0015] In the pure iron powder, the ratio of the peaks of all the planes in an X-ray diffraction pattern to the peak with a plane index of 110 is 0.430 or less. This peak ratio is calculated by X-ray diffraction using the Lieveld analysis method. By keeping the peak ratio at 0.430 or less, it is possible to reduce the hysteresis loss.

[0016] The peak here refers to the peak height (value on the vertical axis, number of counts) in a graph obtained by X-ray diffraction, with the horizontal axis being the diffraction angle 2θ (unit: deg) and the vertical axis being the X-ray intensity (unit: CPS = counts / second). In this X-ray diffraction, the peak heights of six faces, (110), (112), (113), (200), (211), and (220), are detected. In other words, the peak with face index 110 refers to the peak height at face index 110 out of these six faces. Also, the peak of faces in all directions refers to the sum of the peak height values ​​of these six faces.

[0017] One way to make the peak ratio 0.430 or less is to manufacture pure iron powder by gas atomization. In other words, gas is blown onto pure iron powder melted at high temperature, and then it is cooled. The peak ratio can be changed by adjusting the cooling speed.

[0018] Another method for making the peak ratio 0.430 or less is to perform two heat treatments as follows. First, the pure iron melted by atomization is powdered, and then a first heat treatment step is performed. The heat treatment temperature is about 800°C to 900°C. After the first heat treatment, the heat-treated pure iron powder is crushed, and then a second heat treatment is performed at a higher temperature than the first heat treatment, for example, about 900°C to 1000°C. This method can also make the peak ratio 0.430 or less. When the pure iron powder is heat-treated, an inorganic insulating powder such as an alumina powder may be added.

[0019] Furthermore, non-uniform strain is formed in the crystal structure of the pure iron powder. The term "uniform strain" refers to the variation in strain when observing an aggregate of tens of thousands of powder particles and looking at each crystal lattice plane. The non-uniform strain is calculated from the following formula (1) by subjecting the crystal structure of the soft magnetic powder to X-ray diffraction. The value of this non-uniform strain calculated from formula (1) is preferably 0.0030% or less. By keeping the value in this range, it is possible to reduce hysteresis loss.

[0020]

number

[0021] An insulating layer is formed around the pure iron powder, which is a soft magnetic powder. The insulating layer is made of an insulating material, and this insulating material is attached to the periphery of the pure iron powder. As long as the insulating layer is interposed around the pure iron powder, the manner of attachment of the insulating material does not matter. That is, the insulating material may be attached so as to cover the entire periphery of the pure iron powder, or may be attached so as to cover a part of the periphery of the pure iron powder, with a part of the surface of the pure iron powder being exposed. In addition, the insulating material may be attached to the surface of each particle of the pure iron powder, or may be attached to the surface of an aggregate of the pure iron powder, or may be attached so as to have a mixture of these attachment modes.

[0022] As the insulating material, a silane coupling agent, a silicone oligomer, a silicone resin, or a mixture thereof can be used. That is, the silane coupling agent, the silicone oligomer, and the silicone resin may be used alone, or, for example, the silane coupling agent and the silicone oligomer, or the silane coupling agent and the silicone resin may be mixed and used.

[0023] The insulating layer may be a single layer or multiple layers. For example, the insulating layer may be composed of multiple layers divided into layers for each type, or may be composed of a single layer of insulating material in which one type or two or more types are mixed. The insulating material may also contain moisture. In this embodiment, an insulating layer containing a silane coupling agent and silicone resin is formed around the pure iron powder. Note that the moisture evaporates by going through the molded body heat treatment process described later, so it does not remain as an insulating layer.

[0024] As the silane coupling agent, aminosilane-, epoxysilane-, and isocyanurate-based silane coupling agents can be used, and in particular, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, and tris-(3-trimethoxysilylpropyl)isocyanurate are preferred.

[0025] As the silicone oligomer, methyl-based or methylphenyl-based ones having an alkoxysilyl group and no reactive functional group, epoxy-based, epoxymethyl-based, mercapto-based, mercaptomethyl-based, acrylic methyl-based, methacrylic methyl-based, vinylphenyl-based ones having an alkoxysilyl group and a reactive functional group, or alicyclic epoxy-based ones having a reactive functional group instead of an alkoxysilyl group, etc. can be used. In particular, by using a methyl-based or methylphenyl-based silicone oligomer, a thick and hard insulating layer can be formed. In addition, in consideration of the ease of forming the insulating layer, a methyl-based or methylphenyl-based one having a relatively low viscosity may be used.

[0026] Silicone resin is a resin that has a siloxane bond (Si-O-Si) as its main skeleton. By using silicone resin, it is possible to form a coating with excellent flexibility. Silicone resin can be methyl-based, methylphenyl-based, propylphenyl-based, epoxy resin-modified, alkyd resin-modified, polyester resin-modified, rubber-based, etc. Among these, when using methylphenyl-based silicone resin in particular, it is possible to form an insulating layer with little loss on heating and excellent heat resistance.

[0027] Examples of moisture include water and ethanol. The moisture is added after mixing the soft magnetic powder with a silane coupling agent, silicone resin, etc., or at the initial stage of drying the silane coupling agent, silicone resin, etc. The moisture is added by dispersing in a mist or spray, or by dripping fine droplets. The addition of moisture improves the hydrolysis and condensation reactions required for the silane coupling agent, etc., and improves the strength of the core.

[0028] A lubricant is added to the pure iron powder surrounded by the insulating layer, and the powder core is produced through a pressure molding process and a heat treatment process for the compact. Examples of the lubricant include stearic acid and its metal salts, as well as ethylene bis stearamide, ethylene bis stearamide, and ethylene bis stearate amide.

[0029] The pressure molding process is a process for producing a powder compact by pressure molding the pure iron powder on which the insulating layer has been formed. First, the pure iron powder is filled into a die, and then the pressure during molding is 10 to 20 ton / cm. 2 The mixture is pressed at a pressure of 1000 MPa to obtain a green compact.

[0030] In the compact heat treatment process, heat treatment is performed in a non-oxidizing atmosphere such as nitrogen gas, a mixed gas of nitrogen and hydrogen, or a low-oxygen atmosphere such as 0.01%, at a temperature of 600°C or higher and lower than the temperature at which the insulating layer formed around the pure iron powder is destroyed (e.g., 850°C).

[0031] (effect) As described above, the soft magnetic powder of the present embodiment includes pure iron powder, and the pure iron powder has an X-ray diffraction ratio of the peaks of all directional planes to the peak with plane index 110 of 0.430 or less. This makes it possible to reduce hysteresis loss.

[0032] In addition, the pure iron powder is a water atomized powder or a gas atomized powder. The water atomized powder has an irregular shape, while the gas atomized powder has a shape close to a sphere. That is, the shape is different from that of the flat powder. In the case of flat powder, it is common to give orientation because the magnetic properties are improved by flowing the magnetic flux in the long side direction. Therefore, there is a tendency to promote the growth of only a specific face among the six faces detected by X-ray diffraction. However, unlike flat powder, water atomized powder or gas atomized powder is preferable to have no anisotropy because it is desired that the magnetic flux flows to the same extent regardless of the direction from which the magnetic flux flows. The present invention suppresses the peak of the face index 100 to promote the growth of other faces and grow overall. In other words, it does not promote the growth of only a specific face. Therefore, it is particularly effective in the case of water atomized powder or gas atomized powder that is not a flat powder.

[0033] (Example) The present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0034] Soft magnetic powders of Examples 1 to 4 and Comparative Examples 1 to 10 and dust cores using these soft magnetic powders were produced. In Examples 1 to 4 and Comparative Examples 1 to 10, pure iron powders were used as soft magnetic powders having different peak ratios of all directional planes to the peak with plane index 110 in X-ray diffraction. The peak ratios in Examples 1 to 4 and Comparative Examples 1 to 10 are as shown in Table 1 below. The pure iron powder was sieved with the mesh sizes shown in Table 1.

[0035] Here, the crystal structure of the sieved pure iron powder was observed. Specifically, the ratio of the peaks of all directional planes to the peak with a plane index of 110 and the non-uniform distortion were measured by X-ray diffraction. A fully automatic X-ray diffractometer (BRUKER D2 PHASER: Cu tube, X-ray wavelength λ=0.154 nm) was used as the X-ray diffractometer. As shown in Table 1, soft magnetic powders of Examples 1 to 4 and Comparative Examples 1 to 10 were produced, each of which has a different ratio of the peaks of all directional planes to the peak with a plane index of 110. The process of producing the powder magnetic core described below is common to Examples 1 to 4 and Comparative Examples 1 to 10.

[0036] Next, 0.5 wt% of a silane coupling agent, 2.2 wt% of a methylphenyl silicone resin, and 0.5 wt% of water as moisture were added and mixed into the sieved pure iron powder, and then dried at a temperature of 150°C for 2 hours. As a result, an insulating layer containing the silane coupling agent and the methylphenyl silicone resin was formed around the pure iron powder.

[0037] Then, for the purpose of crushing, the powder was passed through a sieve with an opening of 500 μm, and 0.5 wt% zinc stearate was added as a lubricant. The lubricated pure iron powder was then filled into a container with an outer diameter of 20.85 mm, an inner diameter of 12.4 mm, and a height of 5.0 mm, and compacted under a molding pressure of 10.5 ton / cm. 2 Finally, the produced powder compact was heat-treated at 620° C. for 2 hours in a hydrogen atmosphere with a hydrogen concentration of 5%, to produce a powder magnetic core.

[0038] A primary winding of 30 turns and a secondary winding of 30 turns were wound with a copper wire of φ0.5 mm around the powder magnetic cores of Examples 1 to 4 and Comparative Examples 1 to 10 produced as described above, and the hysteresis loss was measured. The measurement conditions were a frequency of 20 kHz and a maximum magnetic flux density Bm=200 mT. A BH analyzer (Iwatsu Measurement Corporation: SY-8219) was used as the magnetic measuring device. The hysteresis loss coefficient was calculated by the least squares method using the following equations (1) to (3), and the hysteresis loss was finally calculated.

[0039] Pcv = Kh×f + Ke×f2 (1) Ph = Kh × f (2) Pe = Ke × f 2 (3) Pcv: Iron loss Kh: Hysteresis loss coefficient Ke: Eddy current loss coefficient f: frequency Ph: Hysteresis loss Pe: Eddy current loss

[0040] The above measurement results are shown in Table 1 and Figures 1 to 3. Figure 1 is a graph showing the relationship between the ratio of the peaks of all oriented planes to the peak of the plane index 110 and non-uniform strain. Figure 2 is a graph showing the relationship between non-uniform strain and hysteresis loss. Figure 3 is a graph showing the relationship between the ratio of the peaks of all oriented planes to the peak of the plane index 110 and hysteresis loss.

[0041] [Table 1]

[0042] 1, in Examples 1 to 4 in which the ratio of the peak of the planes in all directions to the peak of the plane index 110 is 0.430 or less, the value of non-uniform strain is 0.0030 or less, and it was confirmed that the non-uniform strain is greatly reduced compared to Comparative Examples 1 to 10. In particular, it was confirmed that when the peak ratio is made smaller than 0.400, the value of non-uniform strain is smaller than 0.0010.

[0043] In addition, the hysteresis loss in Examples 1 to 4, in which the non-uniform strain was greatly reduced, was 1070 (kW / m 3 ), and it was confirmed that the hysteresis loss was reduced more than that of Comparative Examples 1 to 10. In particular, when comparing Example 4 and Comparative Example 1, the peak ratio differs by only 0.003, but the non-uniform strain value is significantly different, and Example 4 is 100 (kW / m 3It was confirmed that the hysteresis loss could be reduced by 1060 (kW / m 3 ), and it was confirmed that the hysteresis loss was further reduced. As described above, it was confirmed that in Examples 1 to 4, in which the ratio of the peaks of the planes in all directions to the peak of the plane index 110 was 0.430 or less, the hysteresis loss was reduced.

[0044] (Other embodiments) In this specification, an embodiment of the present invention has been described, but this embodiment is presented as an example and is not intended to limit the scope of the invention. The above-mentioned embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the scope of the invention. The embodiment and its modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and gist of the invention.

Claims

1. Equipped with pure iron powder, The pure iron powder has an X-ray diffraction ratio of the peaks of all planes in all directions to the peak of plane index 110 of 0.430 or less; A soft magnetic powder characterized by:

2. The pure iron powder is a water atomized powder or a gas atomized powder; The soft magnetic powder according to claim 1 ,

3. Contains the soft magnetic powder according to claim 1 or 2; A powder magnetic core characterized by:

Citation Information

Patent Citations

  • High-temperature sliding material

    JP1984029819A

  • Iron powder for dust core

    JP2014210966A

  • Soft magnetic material, dust core using soft magnetic material, reactor using dust core, and method for producing dust core

    JP2017011271A

  • Soft magnetic powder, powder magnetic core constructed with the soft magnetic powder, manufacturing method of soft magnetic powder and manufacturing method of powder magnetic core

    JP2020153002A

  • Dust core and process for producing same

    WO2011077601A1